Объяснение:
1) CaO + 2HCL = CaCL2 +H2O
( н) (р) (р) (н)
CaO+ +2H+ +2CL^- = Ca^2+ + 2CL^- + H2O
СaO +2H^+ =Ca^2+ +H2O
2) Zn + H2SO4 = ZnSO4 +H2
(н) (р) (р) (н)
Zn + 2H^+ +SO4^2- = Zn^ 2+ +SO4^2- + H2
Zn + 2H^+ =Zn^2+ +H2
3) 2HBr + Mg(OH)2= MgBr2 +2H2O
(р) (н) (р) (н)
2H^+ +2Br^- + Mg(OH)2 = Mg^ 2+ + 2Br^ - +2H2O
2H^+ + Mg(OH)2 = Mg^2+ +2H2O
4) 2HNO3 +Na2SiO3 = 2NaNO3 + H2O + SiO2
(р) (р) (р) (н) (н)
2H^+ + 2NO3^- + 2Na^+ +SiO3^2- = 2Na^+ +2NO3^- +H2O +SiO2
2H^+ SiO3^2- = H2O +SiO2
1. Al2O3 + 6HCl = 2AlCl3 + 3H2O
Al2O3 + 6H+ + 6Cl- =2Al 3+ + 6Cl - + H2O
Al2O3 + 6H+ = 2Al 3+ + H2O
2. Fe(OH)2 + 2HNO3 = Fe(NO3)2 + 2H2O
Fe(OH)2 + 2H+ + 2NO3- = Fe 2+ + 2NO3 - + 2H2O
Fe(OH)2 + 2H+ = Fe2+ + 2H2O
3. Zn(OH)2 + NaOH = Na2ZnO2 + 2H2O